Impact of Nano and Micro Analysis Studies on the Sustainability of Products and Components - Nour, Ahmed A. (AUC Knowledge Fountain, 2024)
Abstract The emergence of Nano and Micro analysis has marked the beginning of a new era of substantial advancements across research disciplines and various industries. Utilizing Nano and Micro analysis methods and techniques holds a profound promise for advancements of materials, Healthcare and Medicine, Agricultural applications, Food science, Construction and Civil Engineering, Environmental Sustainability, Energy, and Transport & Automobile. Further, Nano and Micro analysis techniques and methods have made a substantial contribution to the 17 SDGs (Sustainable Development Goals). This work outlines a research endeavor that aims to investigate the impact of Nano and Micro analysis on the sustainability of products and components. This work starts with a comprehensive introduction to Nano and Micro analysis techniques, elucidating their capabilities to characterize materials at the nanoscale and microscale. The introduction classifies Nano and Micro analysis techniques and briefly discusses the functions of a selection of the most well-known instruments. The focus of this research is to explore how Nano and Micro analysis enhances the sustainability of products. We conducted a comprehensive literature review to identify the gaps in previous research works. In addition, this investigation focusses on how Nano and Micro analysis statistically contribute to achieving the 17 SDGs. To achieve a meaningful statistic, we developed a well-structured research methodology and research framework. The study outlines a framework to collect usage data from a reputed Nano and Microtechnology Research Center in Cairo. The collected data were thoroughly analyzed and correlated with the 17 SDGs so that the research outcome identifies the gaps and areas of strength for further actions. Using both literature review and the analyzed data from the case study, this investigation explored the impact of Nano and Micro analysis studies on the Environmental, Social, and Economic aspects, which together form the three pillars of sustainability. Further, through conducting in-depth research, this study sought to produce a valuable insight that can be informative for industry and different research disciplines. Also, this study sought to be a valuable guidance for policymakers. Ultimately, this research work seeks to contribute to a more sustainable future.